Optimizing Osteoarthritis Management: A Systematic Review of Hydrotherapy's Impact on Symptoms and Quality of Life - Tata Mahyuvi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Introduction: Osteoarthritis (OA) is a prevalent type of arthritis, particularly among the elderly, and is a leading cause of disability in older adults. Reduced physical activity in OA patients often results in psychological disturbances when visiting healthcare facilities, contributing to a significant burden on healthcare services and diminishing individual quality of life. Objective: This study aims to analyze the literature on the effectiveness of hydrotherapy and land-based physical exercise in addressing osteoarthritis (OA) symptoms. Methods: A systematic literature search was conducted using the PubMed, Semantic Scholar, and OpenAlexa databases up to December 2024. Keywords included "Osteoarthritis OR OA," "Hydrotherapy OR Aquatic Therapy OR Foot Soak," and "Exercise OR Physical Therapy”. Results: A total of eight studies met the inclusion criteria, comprising six randomized controlled trials and two quasi-experimental studies. The findings indicate that hydrotherapy significantly reduces pain, improves joint mobility, and enhances quality of life, particularly for patients with difficulty performing land-based activities. Moreover, land-based physical exercises are effective in improving joint function and overall physical performance. The combination of these approaches may provide an optimal solution for OA management, addressing both physical and psychological challenges faced by patients. Conclusion: These findings highlight the importance of incorporating hydrotherapy into OA treatment protocols to improve patient outcomes and quality of care.